Anti-racism legislation in Brazil: the role of the Courts in the reproduction of the myth of racial democracy - Machado, Marta Rodriguez de Assis; Lima, Márcia; Neris, Natália (Revista de Investigações Constitucionais, 2019)
The goal of this paper is to analyze Brazilian anti-racism law in practice, assessing judicial response to cases of racial stigma and insult. We analyzed over 200 cases from 9 Brazilian states involving racial insults and racial disparagement in Brazilian courts of appeal. We find that the judiciary tends to downplay the importance of insult and stigma, often dismissing cases or lowering penalties. This judicial treatment conflicts with the evidence that racial insults are prevalent in society and serve to maintain racial hierarchies. While the judiciary appears to be enforcing anti-discrimination law, the actual decisions show that the legal system fails to recognize and deal with the real dynamics of Brazilian racism thereby reinforcing the myth of Brazil racial democracy.